2013
DOI: 10.1017/s1368980013000967
|View full text |Cite
|
Sign up to set email alerts
|

A food desert in Detroit: associations with food shopping and eating behaviours, dietary intakes and obesity

Abstract: Objective: Currently 67 % of the US population is overweight or obese and obesity is associated with several chronic medical conditions. Geographic areas where individuals lack access to healthy foods have been termed 'food deserts'. The study aim was to examine if area of residence within Metro Detroit was associated with dietary intake, food and shopping behaviours, and BMI. Design: Cross-sectional study. Settings: Participants were recruited in the waiting area of four primary-care clinics. Subjects: Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…In addition to in-store food purchasing behaviors, store utilization behaviors are of interest as well. Review of previous studies focusing specifically on food shopping behaviors suggests that low-income populations may grocery shop less frequently because of the timing of food assistance benefits, which would affect perishable items such as fresh fruits and vegetables 4–6,1117 ; they may have insufficient spatial access (living further away from a grocery store) to supermarkets and grocery stores selling healthful foods 4,5,16,18–21 ; and they may lack transportation to facilitate food shopping 4,22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to in-store food purchasing behaviors, store utilization behaviors are of interest as well. Review of previous studies focusing specifically on food shopping behaviors suggests that low-income populations may grocery shop less frequently because of the timing of food assistance benefits, which would affect perishable items such as fresh fruits and vegetables 4–6,1117 ; they may have insufficient spatial access (living further away from a grocery store) to supermarkets and grocery stores selling healthful foods 4,5,16,18–21 ; and they may lack transportation to facilitate food shopping 4,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The only elements that were not found to be consistently associated with obesity were food insecurity and food deserts from the food environment. The lack of association indicates a resilient response of the population, despite the limitations associated with their low income.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the current issue reflect this heterogeneity. In a study conducted in Melbourne, Australia, for example, women who lived further from the nearest supermarket were less likely to consume low amounts of fast food (12) , but living in a food desert in Detroit, USA, was not significantly associated with residents' BMI (13) . Food cost is another important aspect of the food environment, and in this issue Holm et al (14) found a moderate reduction in the incidence of cardiovascular diseases and some cancers in Denmark when the rate of value-added tax on fruit and vegetables was halved and the tax on fats was increased.…”
Section: Physical and Economic Accessmentioning
confidence: 97%